PENGEMBANGAN LKPD BERDIFERENSIASI BERBASIS GAYA BELAJAR DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU PADA SISWA KELAS VII - Ni Ketut Werestini; Putu Wulandari Tristananda; L Eka M Julianingsih P (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This development research aims to (1) describe the design of differentiated worksheets; (2) analyze the validity of differentiated worksheets; (3) analyze the practicality of differentiated worksheets in the Hindu Religious Education subject for seventh-grade students at SMP Negeri 2 Sawan. This study employed the Design and Development Research (DDR) method, comprising the stages of analysis, design, development, and evaluation. The research subjects included subject matter experts, media experts, language experts, Hindu Religious Education teachers, and seventh-grade students at SMP Negeri 2 Sawan. The results of this study indicate that worksheets accommodate diverse learning styles; therefore, differentiated worksheets were developed for the topic of Historical Remnants of the Hindu Religion in Indonesia, incorporating three learning activities: visual activities involving observing images; auditory activities involving listening to audio containing conversations; case studies covering material on historical remnants of the Hindu religion in Indonesia; and kinesthetic activities through simple practical exercises. Based on expert evaluations, these worksheets received a “highly valid” rating, with a content validity percentage of 96,5%, a media validity percentage of 95%, and a language validity percentage of 88.75%. The practicality test results from teachers yielded a percentage of 98.6%, the one-on-one test 90.6%, and the small-group test 97.75%, all categorized as “highly practical.” These results indicate that the differentiated worksheets developed are highly valid and practical for use in the learning process, thereby supporting meaningful, learner-centered learning. ABSTRAK Penelitian pengembangan ini bertujuan untuk mendeskripsikan rancang bangun LKPD berdiferensiasi, menganalisis validitas LKPD berdiferensiasi, dan menganalisis kepraktisan LKPD berdiferensiasi pada mata pelajaran Pendidikan Agama Hindu siswa kelas VII di SMP Negeri 2 Sawan. Penelitian ini menggunakan metode Design and Development Research (DDR) dengan tahapan analisis, perancangan, pengembangan, dan evaluasi. Subjek penelitian meliputi ahli materi, ahli media, ahli bahasa, guru Pendidikan Agama Hindu, serta peserta didik kelas VII SMP Negeri 2 Sawan. Hasil dari penelitian ini menunjukkan bahwa LKPD memiliki gaya belajar yang beragam, sehingga dikembangkan LKPD berdiferensiasi pada materi Peninggalan Sejarah Agama Hindu di Indonesia, yang memuat tiga aktivitas pembelajaran, yaitu aktivitas visual berupa mengamati gambar, auditori berupa mendengarkan audio yang memuat percakapan, studi kasus yang memuat materi tentang peninggalan sejarah agama Hindu di Indonesia, serta kinestetik melalui praktik sederhana. Berdasarkan penilaian dari para ahli, diperoleh kategori sangat valid dengan persentase validitas ahli materi sebesar 96,5%, ahli media sebesar 95%, dan ahli bahasa sebesar 88,75%. Hasil uji kepraktisan oleh guru memperoleh persentase sebesar 98,6%, uji one to one sebesar 90,6%, dan uji small group sebesar 97,75% dengan kategori sangat praktis. Hasil tersebut menunjukkan bahwa LKPD berdiferensiasi yang dikembangkan dinyatakan sangat valid dan praktis digunakan dalam proses pembelajaran, sehingga dapat mendukung pembelajaran yang bermakna dan berpusat pada peserta didik.